База даних для підтримки діяльності маркетолога в онлайн-спільнотах - Пелещишин, Оксана (Видавництво Львівської політехніки, 2012)
The article examined the activities of marketing in online communities, the proposed use of a database for recording and analysis of marketing communications.
Keywords: онлайн-спільноти; маркетингові комунікації